Excellence Towards Global Competitiveness: A View on Cultural Integration - Wang Ke (International Journal of Management and Education in Human Development, 2022)
This paper is a personal note on cultural transmission, which introduces the main conceptual issues which are of relevance to the study of the cultural integration patterns of foreign students studying in another country and their interaction with others. More specifically, this paper briefly discusses the different patterns of cultural integration in a university environment.